코로나19 전후 영유아기 자녀를 양육하는 맞벌이 부부의 우울 잠재프로파일 분석 - 방지원(Jiwon Bang); 유성경(Sung-Kyung Yoo) (가정과삶의질연구, 2024)
본 연구는 코로나 전후 맞벌이 부부의 우울이 어떠한 잠재프로파일로 분류되는지 확인하고 각 유형의 특징이 무엇인지 살펴보았다. 소득, 지각된 배우자 지지, 대처와 코로나 위험 지각이 잠재프로파일 분류에 영향을 미치는지 확인하고, 잠재프로파일별삶의 만족도와 결혼만족도의 차이가 나타나는지 확인하였다. 연구 결과, 코로나 전 맞벌이 부부의 우울은 ‘부부 저우울 집단’(82.56%, 아내 CES-D 13.12점, 남편 CES-D 13.56점)과 ‘아내 고우울 집단’(17.43%, 아내 CES-D 33.66점, 남편 CES-D 20.66점)으로 분류되었다. 코로나 이후에는 ‘부부 저우울 집단’(61%, 아내 CES-D 10.97점, 남편 CES-D 9.48점), ‘남편 고우울 집단’(19.2%, 아내 CES-D 17.36점, 남편 CES-D 28.84점), ‘아내 고우울 집단’(19.8%, 아내 CES-D 31.36점, 남편 CES-D 16.71점)으로 분류되어코로나 이전에는 없었던 ‘남편 고우울 집단’이 새로 출현하였다. 코로나 전 아내의 대처와 지각된 배우자 지지가 잠재프로파일분류에 영향을 주었으며, 코로나 후에는 아내의 대처, 지각된 배우자 지지뿐 아니라 남편의 대처, 지각된 배우자 지지가 유형 분류에 영향을 주었다. 코로나 전후 맞벌이 부부의 우울 잠재프로파일에 따라 삶의 만족도와 결혼만족도의 차이가 나타나는지 살펴보았는데, 코로나 전 부부 저우울 집단의 부부 삶의 만족도와 결혼만족도는 아내 고우울 집단보다 유의하게 높게 나타났다. 코로나이후에는 부부 저우울 집단의 아내와 남편의 삶의 만족도, 결혼만족도가 나머지 집단보다 유의하게 높았다. 다만 남편 고우울집단 아내의 삶의 만족도와 결혼만족도 모두 아내 고우울 집단과 유의한 차이를 보였지만, 남편은 삶의 만족도에서만 유의한 차이가 나타나 결혼만족도에 대한 부부의 성차가 확인되었다. The purpose of this study is to examine depression of couples in depth before and after COVID-19 using latent profile analysis. As a result, the depression of double-income couples before COVID-19 was classified into the "Low depression couple" (82.56%) and the "High depression wife" (17.43%). The "Low depression couple" is understood as a healthy group that does not experience significant depression. The wife of the "High depression wife" experiences severe depression and the husband experiences a minor level of depression. After COVID-19, the depression of double-income couples was classified into “Low depression couple”(61%), "High depression husbands" (19.2%), and “High depression wife”(19.8%). A new "High depression husband," which did not exist before COVID-19, appeared, and the husband of this group showed severe depression, while his wife showed mild depression. For the “Low depression couple”, both wife and husband showed no symptoms of depression, while in the case of the "High depression wife," the wife showed severe depression and the husband showed mild depression. Before COVID-19, the wife’s coping and perceived spousal support affected the classification of latent profiles, and after COVID-19, not only the wife’s coping and perceived spousal support but also the husband’s coping and perceived spousal support affected the classification of types. Before COVID-19, the life satisfaction and marital satisfaction of the “Low depression couple” were significantly higher than that of the “High depression wife”. After COVID-19, the life satisfaction and marital satisfaction of wives and husbands in the “Low depression couple” were significantly higher than that of the rest of the group. However, the wife of the “High depression husbands” group showed a significant difference in both life satisfaction and marital satisfaction compared to the “High depression wife”, but the husband only showed a significant difference in life satisfaction, confirming the couple’s gender difference in marital satisfaction. KCI Citation Count: 1